Wynagrodzenie w kontekście przepisów podatkowych. Analiza porównawcza Polska – Niemcy - Nyk, Mariusz (Gospodarka w Praktyce i Teorii, 2013)
Reward presents this economic largeness, which (who) wakes up huge argumentations obliged own in context of feature that, determinant eats forming, significant, as well as correct definition. It is not possible to ascertain directly, that countries are characterized about superior degree of economic development more restrictive, as well as in range of taxation of reward liberal politics fiscal. Range is determinant for formulating tax system about differentiated character having feature not only social stymulant but also economic ( fiscal ). Elaboration has appearance of difference on purpose and between system of taxation of reward in poland similarities and in Germany. Thesis, which will be verified in the present elaboration, there is following in development among -economic significant socially polish.